The Adaptive Challenges of Curriculum Implementation: Insights for Educational Leaders Driving Standards-Based Reform - Katie Pak; Morgan S. Polikoff; Laura M. Desimone; Erica Saldívar García (SAGE Publishing, 2020)
The ambitious goals of standards-based reform call for both technical and adaptive leadership to address problems of practice involving the technical and adaptive alignment of teachers' instruction to the standards. Thus, standards-aligned curriculum implementation necessitates both types of strategies; otherwise, adaptive challenges will persist. In this study, we analyze case studies of four districts where new English Language Arts and math curricula were recently adopted to help align teachers' practice with their state's English Language Arts and math standards. We draw from interviews with district leaders, principals, instructional coaches, and teachers to illustrate how mostly technical strategies for curriculum implementation do little to address the adaptive challenges that prevent teachers from fundamentally shifting their practice to be more aligned to the standards and to meet the needs of all learners. We conclude with a set of insights and implications for educational leaders approaching curriculum implementation in both technical and adaptive ways.